Religious and Spiritual Communities Must Adapt or Die: Surviving and Thriving during Challenging Contemporary Times - Plante, Thomas G. (Religions, 2024)
Current trends within both religious and secular communities suggest that contemporary times mean that people spend more time alone than with others. Community engagement in general has been declining, while religious and spiritual community engagement in particular has dropped off significantly in recent decades, and most especially following the COVID-19 global pandemic. Although humans are social beings and benefit from community engagement, we tend to avoid or minimize our affiliations and associations, including our religious and spiritual ones today. Religious and spiritual communities must adapt to changing times or risk becoming irrelevant, diminishing further, and losing their sustainability to continue with their activities and services. Religious communities might wish to consider the best state-of-the-art evidence-based practices to engage their members, as well as appeal to those who might be interested in joining with them. There are many mental and physical health benefits to active engagement with spiritual religious practices and communities. The world could use more rather than less community engagement, including religious and spiritual engagement, during our challenging contemporary times.